DeadEndia. Book 2, The broken halo - Steele, Hamish (Deadendia, 2023)
As Dead End reopens, hotel manager Norma is determined to leave the ghosts of the past where they belong, but with her friendship with Barney up in the air and the visiting angels and demons causing chaos, Norma soon discovers unwanted ghosts can appear at any moment, especially your own.